Scale-based cluster formation for multi-agent systems with mismatched disturbances. Issue 13 (September 2019) - Jin, Tao; Liu, Zhi-Wei; Zhou, Hong; Ge, Ming-Feng
Abstract: This paper studies scale-based cluster formation problem of multi-agent system (MASs) under mismatched disturbances. A distributed sliding mode control with a disturbance observer is proposed to solve the aforementioned problem in the leaderless and leader-follower cases. The proposed control strategy provides satisfactory robust performance under mismatched disturbances and is thus more applicable to complicated formation control tasks. Finally, simulation results are provided to justify the validity of the proposed method.